Case report: Lymph node metastases of breast cancer and thyroid cancer encountered in axilla - Li, Rihan; Zhang, Qingfu; Feng, Dongdong; Jin, Feng; Han, Siyuan; Yu, Xinmiao (Frontiers in Oncology, 2022)
Occurrences of breast cancer and thyroid cancer metachronously or synchronously are common for females, but axillary lymph node metastasis from both cancers is rarely seen. We report a patient who found two metastatic lymph nodes from papillary thyroid carcinoma after axillary lymph node dissection with mastectomy. Papillary thyroid carcinoma diagnosis was ensured after thyroidectomy. A literature review revealed that even co-occurrence of breast cancer and thyroid cancer is not rare, but the etiology behind this phenomenon is not unelucidated well. Genetic disorders, thyroid dysfunction, and hormone receptors may be relevant. Considering the rareness of axillary lymph node metastasis of thyroid cancer, adjuvant therapy and surgery treatment for this kind of case should be considered elaborately.